The Effectiveness of Multimodal Gamified Learning Platforms in Enhancing Student Engagement and Computational Thinking Skills in K-12 Classrooms: A Randomized Controlled Trial - Safar, Muh.; A. Tamagola, Rendi Hadian; Sitti Hasnah; Opan Arifudin; Ika Kartika (International Journal of Educational Research Excellence, 2026)
This study investigates the effectiveness of a multimodal gamified learning platform in enhancing student engagement and computational thinking (CT) skills in K–12 classrooms. Building on evidence that gamification and multimodal learning can positively influence motivation and complex skill development, the research adopts a randomized controlled trial (RCT) design with an embedded qualitative approach. Two parallel classes at each grade level (upper primary and lower secondary) were randomly assigned to either an intervention condition, using a multimodal gamified platform, or a control condition, receiving conventional instruction. Data were collected through classroom observations, student focus group interviews, teacher interviews, and artefact analysis of students’ digital work. Thematic analysis was used to generate a comprehensive qualitative account of how gamified and multimodal affordances shaped students’ behavioral, emotional, and cognitive engagement, as well as their CT practices (decomposition, abstraction, algorithmic thinking, and debugging). Findings suggest that the multimodal gamified platform fostered sustained engagement, promoted collaborative problem-solving, and supported more explicit CT articulation compared to traditional instruction. However, the study also identifies challenges related to cognitive overload, inequities in participation, and teachers’ design capacity. Implications are discussed for the design of constructively aligned multimodal gamified curricula and for professional development in K–12 contexts